The Effect of Role Ambiguity and Organizational Justice on Cyberloafing with Job Stress as a Mediation Variable - Nindy Elsa Megaputri; Lieli Suharti (International Journal of Social Science and Business, 2022)
The development of technology, especially the internet, is beneficial in any case, including work. Despite the many benefits of the internet, its widespread use in the workplace has inadvertently formed a new pattern of deviant behavior called cyberloafing. This study aimed to analyze the effect of role ambiguity and organizational justice on job stress and cyberloafing. The research method used is quantitative by using a questionnaire for data collection. A sample of 104 respondents was taken by accidental sampling technique. The instrument used in this research is a questionnaire in the form of a google form distributed through social media, email, and others. The data analysis technique of this research uses Partial Least Square (PLS) with Smart-PLS software as an analytical tool. Based on the results of the study, it can be concluded that the variables of work ambiguity and organizational justice affect work stress. Role ambiguity and organizational justice were also found to influence cyberloafing behavior. However, this study did not support the research hypothesis about job stress mediating the effect of role ambiguity and organizational justice on cyberloafing.